Social Innovation Education in European Higher Education - Pouliopoulos, Theofilos; Schorer, Antonia; Garefi, Ioanna; Kalemaki, Irene; Galvan, Cristina; Barajas, Mario; Theodoridou, Katerina; Kouros, Thodoris; Fuduric, Morana; Mavrogeni, Stavroula; Wittine, Zoran; Protopsaltis, Aristidis (Proceedings of 12th International Social Innovation Research Conference, 2022)
Social Innovation Education (SIE) is a unique teaching and learning approach that features certain principles. Its contribution according to Rivers et al (2015) is four-fold. It promotes systemic and sustainable approaches to improving society through positive social change. It aims to develop qualities for positive change-making in students, such as those referred to as “attributes for social innovation.” It subsumes the development of employability skills and twenty-first-century skills, while working toward a more sophisticated set of competencies and finally promotes learning on a more critical and socially impactful plane than traditional undergraduate education. (Alden-Rivers, et al., 2015, p. 3) This paper as part of the EC project (BUFSIE) examines the current statues of SIE in HE in five European countries (DE, GR, CY, ES, HR). To capture existing notions and experiences regarding SIE in HEIs, an online survey was conducted with university professors and HEI teaching staff. Particularly, 55 HEI professors, teachers and researchers from 5 countries participated in the online survey and allowed us to map and analyse the context of SI and SIE in HEIs. For the assessment of the current situation, the Assessment for learning Audit Instrument (AfLAi) was selected, due to its usability for the educators’ context. The AfL is a methodology to support schools in conducting site-based reviews of their current knowledge, skills and practices in formative assessment. Our assessment tool has embedded the assessment scale of the AfL and the design philosophy. The utmost goal of this assessment process was to map the context of each university, in order to design the best possible intervention regarding SIE. In other words, “any assessment for which the first priority in its design and practice is to serve the purpose of promoting pupils’ learning” (Black et al., 2002, p. 1). The present assessment tool has been designed to assess the level of awareness and integration of Social Innovation Education (SIE) in the countries that participate in the implementation phase of the BUFSIE project. The assessment process is divided into 3 specific areas, which are of course the design principles of SIE: Student at the center Co-creation process Transformative social action The results revealed that the concept of SIE is a rather new term in the HEIs’ context of our study. In some countries, like in Croatia, it is an emerging field, while in others the existence of SIE elements appears to depend on the discipline or the field of study. However, the perception of both educators and students about SIE is more than positive. In fact, it is so positive that students in particular call for an institutionalization of SIE in the standard curriculum and a connection with the ECTS system